If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2h = 3h + 25 Reorder the terms: -2h = 25 + 3h Solving -2h = 25 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. -2h + -3h = 25 + 3h + -3h Combine like terms: -2h + -3h = -5h -5h = 25 + 3h + -3h Combine like terms: 3h + -3h = 0 -5h = 25 + 0 -5h = 25 Divide each side by '-5'. h = -5 Simplifying h = -5
| 50=6(x-2) | | 8h-10=3h+25 | | -60X+747=300 | | 8x-5=2x+14 | | -60X+747=0 | | -4m+3=-9 | | 507=(-60)(4)+B | | 5+(3x+5)=15 | | 3x^2-20x+75=0 | | -3t+8=-13 | | X+1=3x+21 | | 2y+5=4y-7 | | 45=x+6 | | -25X+350=0 | | 45=x^2-32 | | 5+d=5-d | | 8x+2=4x+2(x-3) | | 3y-8=4 | | 3x+y=2xy | | 6(15x+10)-29-(x-32)=7(11x+11) | | 4y-32=8y | | -25X+350=100 | | -2x-4y=6x+12 | | 9m=4m-10 | | 8x-(2x+5)=4x-17 | | 9m=4m+10 | | -2x+6y=-38 | | 0.5x+6=0.1x+9.2 | | 0.51+0.03=0.4-0.74 | | -5m=0 | | 6-9x=6x-10x-19 | | 3.00X+5.00=50.00 |